The Productivity of Black Soldier Fly (Hermetia illucens) Maggot and Its Decomposability on Various Growing Media - Sulaiman, Abrani; Huda, Nindya Ainun; Rahmadinoor, Rahmadinoor; Herliani, Herliani (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2024)
Maggot is the larva of the Black Soldier Fly (Hermitia illucens) which is one of the alternative feeds that meets the requirements as a source of protein and is often used as a decomposing agent for organic waste. The purpose of the study was to determine the best type of media to increase the production of maggot H. illucens as a potential alternative source of protein for animal feed and as fertilizer. This study was designed using a completely randomized design (CRD) with four treatments and five (5) replications. The treatments tried in this study were as follows P1 = Chicken manure, P2 = Cow manure, P3 = Market waste, P4 = Restaurant waste, as maggot growing media. The results showed that the type of growing media had an effect on maggot production including final weight. final length. total weight of maggot. and protein content. also on the ability to decompose maggot including compost residue, dry matter, ash content, and organic matter. The type of media treatment P4 (restaurant waste) was able to produce the highest production, namely the final weight (0.59 g / head). and the final length (2.39 cm / head) with a total maggot production of 367.8 g / unit. but the type of media treatment P3 (market waste) produced the highest maggot protein content of 60.81%. The highest maggot decomposability was found in P4 (restaurant waste).